Barriers and Opportunities for Sustainable Farming Practices and Crop Diversification Strategies in Mediterranean Cereal-Based Systems - Di Bene, Claudia; Dolores Gómez-López, María; Francaviglia, Rosa; Farina, Roberta; Blasi, Emanuele; Martínez-Granados, David; Calatrava, Javier (Frontiers in Environmental Science, 2022)
Agricultural intensification negatively affects the environment through soil degradation, loss of agrobiodiversity, greenhouse gas (GHG) emissions, and nutrient leaching. Thus, the introduction of crop diversification strategies and alternative management practices is crucial to re-design intensive systems. The overall objective of this study was to improve the understanding of the stakeholders’ perceptions of barriers and opportunities for implementing farming practices and crop diversification strategies in intensive rainfed and irrigated cereal-based cropping systems in Italy. Fifty stakeholders, grouped in farmers and technical agricultural advisors, field technical officers from public agricultural administrations, technical experts from NGOs with experience on farming practices, and researchers in agriculture, were engaged by public consultations to capture their practical knowledge of current farming practices for promoting suitable diversified cropping system, as alternative to intensive systems. The analysis of the stakeholders’ perceptions of barriers and opportunities to the transition of cropping systems towards diversification was done using a multi-criteria decision analysis (MCDA). The most important agro-environmental problem identified by the stakeholders in both the cropping systems was the loss of profitability, associated with the risk of farm abandonment, while minimum tillage, maintenance of vegetation covers, application of organic matter/manure and use of green manure, integrated pest management, and change of rotations were identified as the most adequate and effective practices to be adopted in the case study areas. Crop rotation and legumes were the most adequate diversification strategies selected for the intensive rainfed cereal-based cropping systems, while crop rotations with processing tomato and multiple cropping with short cycle maize and wheat were selected as the most appropriate alternatives for irrigated cereal-based production. Our findings highlight relevant strengths and drawbacks for the implementation of diversified cropping systems under low-input agricultural practices. An important strength is that the crop alternatives selected for the diversification are already cultivated as monocultures and are adapted to the local pedoclimatic conditions, while a major weakness is that few farmers are experts in crop diversification. These results can provide insights to support the planning of agricultural policies at different levels.